"Top-Down" Enterprise Development and COVID-19 Impacts on Gulf Women. Issue 2 (3rd April 2021) - Langworthy, Melissa; Warnecke, Tonia
Abstract: Over the past decade, Gulf Cooperation Council (GCC) states have broadened policy support structures for entrepreneurship. After reviewing the core rationale for Gulf state enterprise promotion, we detail regional challenges facing women's enterprise development, such as the regulatory environment and cultural norms relating to gender roles, then examine how these challenges have been exacerbated by the COVID-19 pandemic. Focusing on the gender responsiveness of state policy responses to the COVID-19 crisis, we analyze state actions around promotion of responsive business environments and consider how the policies enacted will impact female entrepreneurs in each country. Finally, we provide recommendations for strengthening the entrepreneurial ecosystem for GCC women.